Removal of lead(II) from aqueous solution using polyacrylonitrile/zinc oxide activated carbon nanofibers - Misdan, Nurasyikin; Abdullah, Norfadhilatuladha; Tajuddin, Muhamad Hanis; Yusof, Norhaniza; Jaafar, Juhana; Aziz, Farhana (UKM, 2017)
This study aimed to prepare activated carbon nanofibers (ACNFs) from polyacrylonitrile (PAN) and zinc oxide (ZnO) via electrospinning process for removal of lead from aqueous solution. The ACNFs/ZnO were characterized in term of its morphological changes, specific surface area and functional groups analysis using Field Emission Scanning Electron Microscope (FESEM), Brunauer–Emmett–Teller (BET) and Fourier Transform Infrared (FTIR) analysis, respectively. The results showed that the specific surface area (SSA) of the ACNFs/ZnO were higher than the neat ACNFs which were 163.04 m2/g as compared to 67.6 m2/g, accordingly. FESEM analysis illustrated that composite ACNFs possessed more compact fibers with presence of ZnO beads and smaller fiber diameter whereas neat ACNFs possessed more aligned nanofibers with larger fiber diameter. Adsorption study showed that the composite ACNFs possessed higher capacity which was 120.3 mg/g as compared to 77.6 mg/g of neat ACNFs. This excellent adsorption performance of ACNFs PAN/ZnO exhibits the potential of this composite adsorbent to solve the environmental issue of heavy metal contamination.